2012
DOI: 10.1158/1078-0432.ccr-11-2470
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence That γ-Tocotrienol Inhibits the Growth of Human Gastric Cancer and Chemosensitizes It to Capecitabine in a Xenograft Mouse Model through the Modulation of NF-κB Pathway

Abstract: Purpose: Because of poor prognosis and development of resistance against chemotherapeutic drugs, the existing treatment modalities for gastric cancer are ineffective. Hence, novel agents that are safe and effective are urgently needed. Whether g-tocotrienol can sensitize gastric cancer to capecitabine in vitro and in a xenograft mouse model was investigated.Experimental Design: The effect of g-tocotrienol on proliferation of gastric cancer cell lines was examined by mitochondrial dye uptake assay, apoptosis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(92 citation statements)
references
References 43 publications
5
86
1
Order By: Relevance
“…Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion. On the other hand, several studies have reported that γ-tocotrienol showed anti-tumor effects, as well as the potential to induce apoptosis, and to inhibit angiogenesis and metastasis (Henderson et al, 2012;Manu et al, 2012). Our results confirm that at 10 μg/ml of γ-tocotrienol reduced MDA-MB-231 cell invasion.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion. On the other hand, several studies have reported that γ-tocotrienol showed anti-tumor effects, as well as the potential to induce apoptosis, and to inhibit angiogenesis and metastasis (Henderson et al, 2012;Manu et al, 2012). Our results confirm that at 10 μg/ml of γ-tocotrienol reduced MDA-MB-231 cell invasion.…”
Section: Discussionsupporting
confidence: 86%
“…These results were consistent with other agents previously reported, including docetaxel (30), γ-tocotrienol (31), magnolol (32), milk fermented by Propionibacterium freudenreichii (33), triptolide and cisplatin (34).…”
Section: D a Bsupporting
confidence: 93%
“…In the present study, Res also suppressed phosphorylation of NF-κB. Certain studies have found that NF-κB activation is associated with CXCR4 expression (30,31). Furthermore, NF-κB was found to be an important component of the SDF-1/CXCR4 axis (32).…”
Section: Discussionsupporting
confidence: 66%